Interaction between redox regulation, immune activation, and response to treatment in HER2+ breast cancer - Paulo Luz; Sofia Ramos; Maria José Oliveira; João G. Costa; Nuno Saraiva; Ana S. Fernandes (Redox Biology)
In HER2+ breast cancer (BC), neoadjuvant therapy represents an ideal scenario for translational research, considering pathological complete response (pCR) as an endpoint. In these patients, achieving pCR after neoadjuvant therapy is associated with a better prognosis. However, biomarkers are needed to tailor optimal treatment for each patient. Evaluating tumour-infiltrating lymphocytes (TILs) has gained attention in predicting pCR. In the context of metastatic disease, TILs also appear to play a role in predicting outcomes. The interaction between the presence of TILs and reactive oxygen species (ROS) remains an area to be explored. ROS are critical for tumour cell homeostasis, and different levels can trigger differential biological responses in cancer cells and their microenvironment. Nevertheless, the influence of ROS on treatment efficacy and prognosis in patients with HER2+ BC remains to be elucidated. In this article, we reviewed the interplay between treatment response, immune system activation, and ROS production in HER2+ BC and suggested novel areas of intervention and research. We also present a bioinformatic analysis demonstrating that the altered expression of several redox-related genes could be associated with the prevalence of immune cell populations in the tumour microenvironment and with patient survival. New biomarkers are thus suggested and should be further explored to tailor the best treatment to each patient.